Disuffo: Design, prototyping and development of an open-source educational robot - Stefano Di Tore; Michele Todino; Maurizio Sibilio (Firenze University Press, 2019)
The paper presents the results of the design, development, implementation and beta-testing of a customizable educational robot, aimed at fostering the development of digital skills in upper secondary school students and encouraging the development of coding in students attending primary school. Specifically, the robot named "Disuffo" is entirely 3D-printed and is composed almost exclusively by interlocking pieces and mounted by screws. Secondary school students are to be involved in the assembly, mounting and modification of the hardware and software of the robot (the robot already owns a software park) while the primary school children will be engaged in coding tasks using the robot.  The aim of this paper is to describe the implementation experiences already carried out, and to promote the dissemination of the project, encouraging the involvement of potentially readers that may be interested in the future development of the project.   Disuffo: Design, prototipazione e sviluppo di un robot didattico open-source L'articolo presenta il risultato di un lavoro di progettazione, sviluppo, implementazione e beta-testing di un robot didattico personalizzabile, realizzato per favorire lo sviluppo delle competenze digitali di studenti frequentanti la scuola secondaria di secondo grado e per favorire lo sviluppo del coding in studenti frequentanti la scuola primaria. Nello specifico, il robot, battezzato Disuffo, è interamente stampato in 3D ed è composto quasi unicamente da pezzi ad incastro o montabili tramite viti. Disuffo è stato pensato per la scuola secondaria di secondo grado per fini didattici e con lo scopo di essere montato, modificato ed utilizzato sia relativamente alla parte hardware che alla parte logica, con i software in dotazione (il robot possiede già un parco software proprio); per la scuola primaria per favorire lo sviluppo del coding. Scopo del lavoro è quello di descrivere le esperienze di implementazione già effettuate, e di favorire la diffusione del progetto, incoraggiando l'adesione al futuro sviluppo del progetto da parte di lettori potenzialmente interessati.